Análise de campos em substratos de antenas de microfita - Lima, André Lopes de (Universidade Federal Rural do Semi-Árido, 2018)
In this work a study on fields in the substrate of the microfita antennas is approached then the study of the propagation of electromagnetic waves is approached in order to improve the quality of its transmission, some materials used for the substrate were the Ferrite and the fiber material of glass (FR4), where the ferrite has a relative permittivity greater than the relative permittivity of the glass fiber, since the size of the microfine antenna is directly related to the properties of these materials. Depending on the material there may be an increase or decrease in antenna size, calculations to determine antenna sizes were done numerically using the scilab software and the frequency adopted for study was 2.5GHz, the antennas were simulated and modeled through software. The ferrite antenna had a significant reduction in size and their return loss were greatly reduced compared to the FR4 antenna.
Artigo Acadêmico
Keywords: Antena de Microfita; Campo Eletromagnético; Substrato; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA